Dizel motorların doğal gaz motorlarına dönüştürülmesi - Pancar, Fuat (Fen Bilimleri Enstitüsü, 1994)
Günümüzün önemli sorunu haline gelen egzoz ve gürültü emisyonları ve enerji kaynaklarının tükenmesi sonucu olarak bunlara çareler aramak amacı ile birçok çalışmalar, araştırmalar yapılmıştır. Motorların alternatif yakıtlarla çalıştırılmaları araştırılarak bu sorunlara optimum çözümler getirmek istenmiştir. îşte bu çalışmalardan biri de doğal gaz motorları olmuştur. Doğal gaz motorları baştan konstrükte edilebilecekleri gibi mevcut dizel motorlarına çeşitli modifikasyonlar uygulanarak da yapılabilmektedirler. Bu çalışmada dizel motorlarının doğal gaz motorlarına dönüştürülmesi ele alınmıştır. Bu dönüştürme de sadece tek yakıtlı olarak ele alınmıştır çünkü çift yakıtlılar ile yukarıda sıralanan amaçların hepsine ulaşılamamaktadır. Çalışma altı ana bölüm altında toplanmıştır. Birinci bölümde doğal gazın dünyada rezervleri ve kullanılma oranlarından bahsedilmiştir. Dizel motoru ve doğal gaz motorunun aynı enerji miktarını verebilmesi için gerekli yakıt miktarları hesaplanıp karşılaştınlrnışur. İkinci bölümde ise yakıt olarak kullanılan doğal gazın genel özelliklerinden bahsedilmiştir. Üçüncü bölümde doğal gazın taşıt motorlarında kullanılması için depolanması yöntemleri, kullanılan depolama tankları, yeni tip yarikriyojenik tanklar ve avantajları, doğal gazın egzoz ve gürültü emisyonlarından ve doğal gaz motorlu taşıtların sürüş rahatlığından bahsedilmiştir. Dördüncü bölümde dizel motorlarının doğal gaza dönüştürülmelerinde devreye giren etkenler : masraflar, sistemin yaygınlaşması, teknolojik ve çevre faktörleri ele alınmıştır. Beşinci bölümde dönüşüm yöntemlerinden, bu yöntemlerde kullanılan sistem lerden ve elemanlardan bahsedilmiştir. Motor üzerinde yapılan değişiklikler olarak da yakıt sistemi, ateşeme sistemi, yanma sistemi, egzoz sisteminden bahsedilmiştir. Kullanılan yakıtın hava fazlalık katsayısına göre tayin edilen fakir karışımlı ve stokryometrOc motor tipleri de ele alınmıştır. Optimum ateşleme avansının bilgisayar destekli bir otomatik kontrol sistemiyle tayini anlatılmıştır. Altıncı ve son bölümde ise yapılan çalışmadan ortaya çıkan sonuçlar ele alınmıştır. Doğal gaz motorlarının performansları, yakıt sarfiyatları ve doğal gaz motorlarının çeşitli konularda diğer tip motorlarla karşılaştırılmaları yapılmıştır.

In the world of XXI Th. century the great problems are limited energy resources and the pollution getting more important day by day. Forecasts say tliat energy resource will run out in approximately 50 years, obviously humanity has to find other alternative energy resources. Those new resources have to provide energy without any pollution. One of the most important causes of these problems is the vehicles due to their internal combustion engines and to the fuel they use. So use of alternative clean and more economical fuel is frequently considered as an emission control strategy. Natural gas is one of this kind of low emissionned fuels. Natural gas does not need to vaporize before it will bum, therefore cold engine starting is easier and cold start enrichment is not required. This conditions reduce CO emissions. Natural gas is constituted of several hydrocarbon elements. Methane is the most important constituent element of the natural gas. It can reach 95 % of the total natural gas. The other constituents are ethane, propane, butane, C02, N2. But these and their proportions can change according to the place where the natural gas is obtained. Natural gas is transported being compressed or liquefied. And it is stored in the tanks under a pressure of 207 bar on the vehicles. For the security they are filled partially. At the first time until 70 bar, at the second time until 140 bar and at the third time until 207 bar. There is two ways of filling system. The first one is the quick filling which is used generally for the light duty vehicles. The filling time is about 3 - 6 minutes. The second is the slow filling system which is used generally for the heavy duty vehicles and for vehicle groups. The filling time is about 4-8 hours. This filling system is cheaper than the quick filling. The weight and size of the cylinders limit the operational range of the vehicle. A new concept of semicryogenic tank for storage and supply of natural gas into the cylinders of an internal combustion engine is made. It allows the gas to be pressurized before injection and uses the heat entering the tank as the means to evaporate the natural gas introduced in the liquid phase in the tank. To limit the heat transfer to the tank and the gas pressure increase, the semicryogenic tank has to be well insulated. There is two adequate insulating materials on the market. The first one is called Trymer 9501. It is a polyisocryanurate material. The second is called foam glass cellular glass. It is high fire resistant and its high compressive strengths allow the tank to put it in horizontal position in the vehicle vii which is more convenient for vehicles because of the problem of sufficient place. Direct injection of natural gas into the cylinder of the engine represents several advantages : - Improvement in the combustion due to a raster and more complete mixing of the vaporized fuel with air in the combustion chamber where the time for the preparation of the mixture is very short. - The gaseous fuel does not absorb heat from the compressed air for vaporization and this contributes to higher efficiency of the engine. - Preheating the natural gas in the tank it is no need to preheat before injection. The semicryogenic tank has to be also preheated to accelerate the gas pressure increase as required. To maintain the right pressure and temperature of the natural gas, an electronic control is needed. The gas preheating system uses the exhaust gases of the engine so the thermal efficiency is increasing. It is concluded that this new concept of semicryogenic tanks brings facilities for the storage of the natural gas and increases efficiency of the engine with the direct injection of natural gas into the cylinder. For the insulation of the semicryogenic tanks it would be better to use foam glass which has more resistance to fire and to compression. Making engines running with natural gas, to obtain the power already given by existing kinds of engines or better conditions are the target of the work. The best power conditions have been provided by diesel engines. But their emission levels are not as good as their power. In order to reduce the emission levels of existing diesel engines, their conversion to natural gas engines has been done. For the conversion of diesel engines to natural gas engines their is two ways : - Conversion to mixed fuel ( dual fueled ) engines - Spark ignited engines ( mono fueled ) In the past a lot of work has been done on mixed fuel systems in diesel engines, in which the gaseous fuel is mixed with combustion air and the amount of diesel fuel ( pilot fuel ) is accordingly restricted. But their emission levels are not as good as obtained from spark ignited engines. In the conversion operations it is desired to use maximum number of common engine components. In the spark ignited engines all diesel injection equipment is removed from the engine, the combustion chamber modified, a spark ignition system and a gas carburetor are fitted in the engine. In diesel engines burning of the fuel is provided by compressing it with high ratios. This can not be used for natural gas engines because the ignition temperature of the natural gas is higher than the diesel fuel so more higher ratios is required and these ratios may provide detonation. So the ignition system of natural gas engines has to be changed and spark plugs may be used. With regard to spark ignited engines their is two kinds : - Lean burn engines : uses a mixture with air excess ratio ( lambda ) greater viii Than l. - Stoichiometric engines : uses a mixture with air excess ratio ( lambda ) close tol. In order to meet the power demanded, the natural gas input is fixed. The mixture mass flow determines the heat capacity of the mass in the engine cylinder. With stoichiometric engines the calorific energy of the mixture is high and the mixture flow is small. Therefore high temperatures are risen during the combustion so the exhaust gas temperatures are rising. Engine components ( cylinder head, pistons, exhaust gas manifold...) have to be tested carefully and if necessary they have to be changed for the new engine type. The low emission levels can be reached using a three - way catalyst and a closed loop oxygen sensor in the exhaust gas. The oxygen sensor meters continuously the air excess ratio and sends signals to the main electronic controlled system wliich adjusts the gas supply such that the air excess ratio is always varying between desired values around 1. For the lean burn engines conditions are strictly opposite according to stoichiometric engines. Calorific energy of the mixture is low but the mixture flow is high. Engine cylinder pressures are high and their temperatures are low. A lean burn engine is pumping a lot of air without being used for combustion so the lean bum engines equipped with a turbo charged system is recommended to have an efficient breathing and a power output competing with diesel engines. In this case a wastegate is needed for a good torque curve. NOx emission levels have to be low because it is very difficult to reduce them after the conversion of the engine. NOx emissions for the lean burn engines may be reduced to very low levels compared with stoichiometric gas engines. The operation of a prechamber can influence the level of exhaust emissions. An oxidation catalyst CO and HC emissions can be reduced. The flame speed of natural gas is low so misfiring can occur thus detonations too. To prevent this, it is recommended to use more than one spark plug. A combustion prechamber construction is useful for the lean burn engines because with help of this prechamber turbulating the mixture, fine firing is obtained. Volumetric efficiency of the spark ignited engines can be increased by use of a tuned intake system. This system utilizes the combined action of the inertia forces and pressure pulsations to increase the breathing capacity of the engine. By supercharging the spark ignited natural gas engines the intake manifold pressure can be strongly increased which results in a higher power output of the natural gas engine. In this study it has been demonstrated advantages and disadvantages of spark ignited engines. Their advantages are : - Full substitution of diesel fuel - Very low exhaust emission levels - Low noise emission level IX - Less vibrations Disadvantages of the ignited engines : - Costs of more elaborate changes - Natural gas stations are not yet sufficient - Storage of natural gas due to their high weights. So a natural gas vehicle is heavier than the diesel vehicle due to its extra load of the fuel cylinders. - Low speed. The park ignited natural gas engines are converted from diesel engines so the maximum engine speed is restricted. This problem can be solved by rising air excess ratio such that NOx emission levels are not important or modifying the transmission elements of the vehicle. Maximum power is restricted by the NOx emissions. The fueling systems of the natural gas engines are electronically controlled. The electronic system consists of a micro - processor controlled unit integrated into the conventional system. Many sensors like oxygen sensor, lambda sensor are placed in the several parts of the system which is desired to be controlled. These sensors meter, analyze continuously emissions and send the results to the micro - processor. The micro - processor compares signals that it received from several parts of the vehicle with the instructions already stored in its memory. It calculates then error between these figures and sends signals to correct the values of the several parts. The convenient systems are operating in a closed loop control. With this electronically controlled closed loop it is easy to control and optimize many characteristics of the engine components. In this study optimization of the spark advance. It is an adaptive control system which is automatically adjusts ignition timing to the needs of the engine. It sets the timing with respect to an internal map which is defined by the engine at a particular set of operating parameters ( engine speed, load, fuel ambient conditions...). Many of these parameters cannot be measured so they are measured in function of the engine speed for example. The responses of the engine to the small systematic changes in a control parameter to determine appropriate values for that parameter is monitored. The primary response variable monitored is the brake torque. The control system changes a control parameter to produce an increase in torque and corrects the value of the parameter. During the experience when the spark timing is advanced the engine begins to speed up and when the spark timing is retarded slows down again. The micro - processor control system monitors these changes in speed and applies a correction to the spark timing. The system continues to apply the corrections until there is not any change of engine speed during the experience. Finally obtained value of the spark timing which does not change the engine speed is the optimized spark timing. At a fixed fuel rate the resulting spark timing gives to the engine the maximum efficiency. The response of the closed of the control system would be too slow to follow the fast transients. In this case, an open loop system based on easily measured parameters such as speed and load, could be added to make changes quickly during the transients. The closed loop control would then fine tune the spark timing set by the open loop. The open loop spark timing can be updated by the micro - processor if the required spark timing is deviated from the open loop value. Using the same techniques, other parameters can be optimized too. The most important requirement is to give small changes to the parameter without changing the fueling rate of the engine. Conversion of the diesel engines to natural gas engines will be applied to a great number of vehicles if the running costs are lower than the alternatives. The break-even mileage is based on equipment costs and mel price. Equipment costs are strongly related to the rate of sophistication needed. For example, electronically controlled carburetor systems were introduced to enable the lowest emission levels. The addition of electronics and actuator initiated a price increase over conventional system. This price increase causes a decrease in the market volume. The price of the natural gas is very low beside the prices of the other fuels. This make the natural gas engines very economic. But the conversion and equipment costs at the beginning are high. With the time after the conversion of the diesel engine, the costs will be amortized. Even the automotive use of natural gas is beneficial for the vehicle owner there is still the demand for equal performances compared to diesel engines. Important performance uses for successful future use of natural gas in vehicles are : - Exhaust emission levels - Maintenance requirements - Applicability Exhaust emission levels of the natural gas engines as said above are the lowest in types of vehicle engines. This is very important for the environment pollution level. The studies and researches to reduce the emissions to the minimum values is continuing. To be able to keep up with natural gas systems regular maintenance and adjustments have to be avoided. The need for maintenance can be reduced by using components that hardly fail. This can be obtained by a system which uses maximum number of standard components possible. The need for regular adjustments can be avoided by using adaptive electronics in a system that uses the sensors as well as the actuators to fulfill the adaptive needs. To be successful, natural gas systems have to comply the automotive progresses and the future automotive technology. The calibration time of natural gas engine systems have to be short. And the most important thing is the number of the natural gas pumping stations have to be sufficient so that this type of engines can get easily their fuel. When the consumption costs of a natural gas engines and diesel engines are compared, it is seen that natural gas engines are very lower beside diesel engines.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1994
Keywords: Dizel motorlar; Doğal gaz; Doğal gazlı motorlar; Diesel engines; Natural gas; Natural gas engines